Pengaruh Parenting Self-Efficacy, Keterlibatan Orang Tua dalam Pembelajaran Online dan Tiingkat Pendidikan Orang Tua terhadap Hasil Belajar Siswa - Franky Anatoly Tumbol; Ronaldo Kho (LPPM Universitas Terbuka, 2022)
During the COVID-19 pandemic students had to learn at home. In this mode of learning students experienced difficulties in understanding the learning material which impacted on student assignments completion. This condition requires parental involvement in solving the problem. Parental background has effects on the quality of student mentoring. This study aims to determine the impact of parenting self-efficacy, parental involvement in online learning, and parental education level on student learning outcomes. The population of this study was all parents (mothers) of active students enrolled in the school. This research uses ex post facto research. The Measurement of variabels using a Likert Scale with multiple regression analysis. The results show that the variabel that has the most influence on student learning outcomes is the level of parental education which contributes 68.3%, followed by the variabel of parental involvement of 22.5% and the variabel of parenting self-efficacy of 9.2%.